UNRAVELING USURY: THE CONSEQUENCES OF INTEREST RATES AND ECONOMIC GROWTH - Bawono, Suryaning; Viphindrartin, Sebastiana; Wilantari, Regina Niken; Lestari Widarni, Eny (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The objective of this research is to examine the dynamic interplay of interest rates (usury), economic development, investment, consumption, and labor force participation in Indonesia. The World Bank provided the data, which is utilized for the years 2000 through 2022. We employ a dynamic threshold time series data model in this investigation. The results show that interest rates affect economic growth. When interest rates are low, loans are more affordable, and consumption and investment tend to increase. Conversely, high interest rates can hinder economic growth due to higher borrowing costs. Good economic growth encourages investment and consumption, which in turn strengthens economic growth. In addition, strong economic growth contributes to the creation of new jobs and increased labor force participation. The more people who work, the greater their contribution to economic growth. Increased investment can also accelerate economic growth by creating jobs, increasing productivity, and driving other sectors of the economy. The relationship between interest rates, economic growth, and labor force participation has a significant impact. The interest rate threshold is around 2.772. Above this threshold, changes in interest rates can stimulate or inhibit economic expansion. Rising interest rates can discourage borrowing and investment while falling interest rates encourage spending and investment. Higher labor force participation rates contribute positively to economic growth. Consumption growth also affects overall economic performance.